A new genus for the small shore crab previously known as Brachynotus spinosus (H. Milne Edwards, 1853) (Crustacea: Brachyura: Varunidae), with two new species from southern Australia and Samoa - Davie, Peter J.f.; Ng, Ngan Kee (Zootaxa, 2024)
The Australian southern temperate shore crab known as “Brachynotus spinosus” is found to be an endemic new species. The true B. spinosus (H. Milne Edwards, 1852), described from the Solomon Islands, is considered to be known only from its type locality in tropical Melanesia. A record identified as this species from Samoa in western Polynesia in 1891, is also here described as a new species. The temperate and two tropical sister-species are closely similar morphologically, and are placed into a new genus, Parvonotus. Parvonotus gen. nov. is separated from species of Brachynotus De Haan, 1833, and Hemigrapsus Dana, 1852, based on carapace and male pleon characters. Parvonotus spinosus comb. nov., P. samoensis sp. nov. and P. meridionalis sp. nov. can be separated on differences in carapace shape, leg proportions, and in the case of the latter two species, male pleon shape.